Use of Fungal Mycelium as Biosupport in the Formation of Lichen-Like Structure: Recovery of Algal Grown in Sugarcane Molasses for Lipid Accumulation and Balanced Fatty Acid Profile - Zorn, Savienne; Carvalho, Ana; Bento, Heitor [UNESP]; Gambarato, Bruno; Pedro, Guilherme; da Silva, Ana; Gonçalves, Rhyan; Da Rós, Patrícia; Silva, Messias [UNESP] (MDPI, 2022)
In this study, a lichen-like structure was obtained through the production of a unique biomass, formed by algae cells of Scenedesmus obliquus adhering to the mycelium of filamentous fungal Mucor circinelloides. This structure was composed in two steps; in the first one, microalgal cells and spores were incubated separately, and in the second one, after 72 h of growth, isolated, mature mycelium was harvested and added to cell culture. For spores’ incubation, a culture medium containing only 2 g·L−1 of glucose and minerals was used. This culture medium, with low sugar content, provided a fungal biomass to the anchorage of microalgae cells. WC medium was used without and with sugarcane molasses supplementation for microalgae cells’ incubation. The lichen-type structure that was formed resulted in 99.7% efficiency in the recovery of microalgae cells and in up to 80% efficiency in the recovery of algae biomass in the lichen biomass composition. In addition, the resulting consortium attained a satisfactory lipid accumulation value (38.2 wt%) with a balanced fatty acid composition of 52.7% saturated plus monounsaturated fatty acids and 47.4% polyunsaturated fatty acids. Since fungal species are easy to recover, unlike microalgae, the lichen-like structure produced indicates an efficient low-cost bioremediation and harvesting alternative; in addition, it provides an oleaginous biomass for various industrial applications.
Keywords: Fatty acid composition; Lichen-like structure; Mature mycelium; Mucor circinelloides; Scenedesmus obliquus